Time, Liberal Justice and UK Social Policies - Fitzpatrick, Tony (2004)
While analyses of time have never strayed too far away from those of social justice, and vice versa, this article's premise is that they have so far failed to converge as directly and coherently as they might. The aim of this article is to facilitate a greater degree of convergence by working within a framework of liberal equality and establishing similarities in the work of the two theorists who have gone farthest in bringing the various debates together. These are Robert Goodin and André Gorz and the article explores the respective strengths and weaknesses of their ideas. A liberal theory of socio-temporal justice is derived from their work and is then used to critique some recent developments in UK welfare reform.